COVID-19 in Italy: Performing Power and Emotions - De Blasio, Emiliana; Selva, Donatella (Frontiers in Political Science, 2021)
The article charts the notion of statehood emerging from the COVID-19 pandemic, considering the emotional repertoire and the themes addressed in the government’s crisis communication. The conception and performance of statehood and power in Italy during the COVID-19 emergency rely on four interrelated nodal points: (1) the state’s relationship to citizens, (2) the state’s relationship to regions and local governments, (3) the state’s relationship to politics and the Italian parliament, and (4) the state within international sphere. For each of those nodal points, we have analyzed relevant themes and rhetorical devices following a discourse-historical approach (DHA). Specific efforts have been made to identify the emotional repertoire mobilized by the Italian government in its communication. In the interplay between the dramatic context of crisis and an enduring trend toward the personalization of the government’s leadership, the source of legitimacy has shifted from traditional democratic procedures to the use of emotional capital. The analysis of the Italian government’s communication reveals the features of the emotional capital used during the pandemic, like the ability to display empathy toward citizens’ sufferings, the will to engage in dialog with social stakeholders, confidence in expertise, and the pride and determination to negotiate within the EU. The article concludes that the performance of the prime minister in expressing his emotional states has nurtured the conception of post-COVID statehood, consolidating his individual leadership and flawing the spaces of political conflict.